Explaining the effects of the popularisation of psychological diagnoses on the perceived clinical significance of mental illness: a quantitative study using questionnaires - Fuller, Jared (The IIE, 2020)
Mental health stigma is an everchanging theme because the sources of information that people can learn about mental illness from is ever-expanding. This is especially true for tertiary students who have learned popularised and overly-simplified versions of mental disorders from social media. The majority of the student’s use of popularised sources as the basis of their semantic memory (Social media at 68.8%, Figure 2) and colloquial use of psychodiagnostic terms through metaphors (where 84.4% admitted to using OCD in a colloquial manner, Figure 1) has resulted in a mediocre ability to recall and identify the correct symptomology for three relatively well known mental illnesses (OCD, MDD and BAD). This means that the popularised sources of knowledge have created a deficit between the academic understanding of mental illness and the publics’ understanding of the mental illness (Calsamiglia, 2003)
Keywords: Popularisation; Psychological diagnoses; Clinical significance; Perceptions; Mental illness; Stigma